Clothing is a carrier of cat allergens - D'Amato, Gennaro; Liccardi, Gennaro; Russo, Maria; Barber, Domingo; D'Amato, Maria; Carreira, Josè (Journal of allergy and clinical immunology, 1997)
Clinical and allergologic studies have shown that sensitization to allergens derived from domestic animals (dogs and particularly cats) is an important cause of prolonged airway hyperresponsiveness with allergic respiratory symptoms and is sometimes a risk factor for bronchial asthma attacks leading to emergency department visits. The major cat allergen, Fel d 1, is found universally in homes of patients with respiratory allergy induced by this animal. Significant increases in allergen levels have been detected after simply allowing the cats to leave their holding cages and move about the room. However, Fel d 1 is also present in dust samples from homes and public places where a cat has never been kept. Consequently, not only direct exposure to cats but also indirect contact may be responsible for an allergic sensitization. In fact, many patients who are allergic to cats do not have this animal in their homes. In this trial, to determine whether clothing could be responsible for dispersal of cat allergen, concentrations of Fel d 1 have been quantified in dust samples from clothes of subjects with and without a cat or a dog in their homes.